2014
DOI: 10.1017/s0263574714000642
|View full text |Cite
|
Sign up to set email alerts
|

Worst-case analysis of moving obstacle avoidance systems for unmanned vehicles

Abstract: SUMMARYThis paper investigates worst-case analysis of a moving obstacle avoidance algorithm for unmanned vehicles in a dynamic environment in the presence of uncertainties and variations. Automatic worst-case search algorithms are developed based on optimization techniques, and illustrated by a Pioneer robot with a moving obstacle avoidance algorithm developed using the potential field method. The uncertainties in physical parameters, sensor measurements, and even the model structure of the robot are taken int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…And since their specific code is not publicly available, it is not possible to build directly on their work; for our work, the code will be opensource (for code, see links provided in Section VI) and further research can thus be easily built on it. Srikanthakumar et al in [25] developed an automatic approach to finding worst cases for moving obstacle avoidance algorithms based on simulations and optimization techniques (one of which is a GA). However, their optimization problem has only one objectiveto find a worst case situation that causes a collision.…”
Section: Fig 1 Overview Of the Testing Methods That Combines Agent-bamentioning
confidence: 99%
“…And since their specific code is not publicly available, it is not possible to build directly on their work; for our work, the code will be opensource (for code, see links provided in Section VI) and further research can thus be easily built on it. Srikanthakumar et al in [25] developed an automatic approach to finding worst cases for moving obstacle avoidance algorithms based on simulations and optimization techniques (one of which is a GA). However, their optimization problem has only one objectiveto find a worst case situation that causes a collision.…”
Section: Fig 1 Overview Of the Testing Methods That Combines Agent-bamentioning
confidence: 99%
“…[26]- [30]. From existing and rapidly evolving types of advanced driver assistance systems (ADAS) to the high-level automation intelligent unmanned driving vehicle [31]- [33], the goal of fully intelligent transportation technology is drawing research attention using multi-sensor information fusion technology [34]- [38]. This is different to Front Collision Warning which only warns the potential collision risks [39]- [42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results show that the algorithm adapts to the characteristics of high-speed USVs and can guide high-speed USVs (≥ 20 ≥ 20 math container loading MathJax knots) in realising safe navigation in real marine environments. But this method has the problem of low obstacle avoidance; according to Srikanthakumar and Chen (2015), the paper investigates worst-case analysis of a moving obstacle avoidance algorithm for unmanned vehicles in a dynamic environment in the presence of uncertainties and variations. It is demonstrated that a local nonlinear optimisation method may not be adequate, and global optimisation techniques are necessary to provide reliable worst-case analysis.…”
Section: Introductionmentioning
confidence: 99%